Gamma interferon enhances macrophage transcription of the tumor necrosis factor/cachectin, interleukin 1, and urokinase genes, which are controlled by short-lived repressors (The Rockefeller University Press, 1986)
Exposure of mouse resident and thioglycollate-elicited peritoneal macrophages to IFN-gamma leads to a marked increase in the TNF-alpha (tumor necrosis factor/cachectin), IL-1 and u-PA (urokinase-type plasminogen activator) mRNA levels. Nuclear run-on experiments show that IFN-gamma acts by enhancing the transcription of these three genes. Transcription of these three genes is also rapidly and transiently induced by cycloheximide, an inhibitor of protein synthesis, indicating that they are under the control of short-lived repressors.